Murder in an Italian café - Falco, Michael (Mystery writer) (Falco, Michael (Mystery writer). Bria Bartolucci mystery ;, 2024)
Though she still misses her late husband, Carlo, Bria couldn't be happier that their dream bed and breakfast, Bella Bella, is humming along nicely. Of course, even on the stunning Amalfi Coast, things seldom run smoothly. Like Bria's mother and mother-in-law dueling over a suitable communion site for Bria's eight-year-old son Marco. Bria's also juggling the demands of the famous Chef Lugo, his producer, Massimo, and Pippa, a member of the production crew who is staying at Bella Bella for a nice, long-term stay... Until Lugo mysteriously dies on-camera, a victim of apparent murder. But finding out who wanted him gone is no stroll on the beach. Bria soon learns that Chef Lugo's multi-media empire is at a make-or-break tipping point, and Lugo himself had racked up any number of enemies--financial, professional... and very personal. Now to save her friend's café from a ruined reputation, Bria must delve into the glittering surface of false alibis, pretty lies, and not-so-glamourous hidden identities to catch a murderer determined to serve up another victim... --